Creatine monohydrate supplementation: Considerations for cognitive performance in athletes. - Machek, S. B.; Bagley, J. R. (Strength and Conditioning Journal, 2018)
Creatine monohydrate supplementation can increase total creatine and phosphocreatine stores for resynthesis of adenosine triphosphate. Although most existing literature has investigated creatine to improve strength and body composition, it has also been shown to promote brain energy homeostasis and improve cognitive parameters. This may be another mechanism for performance enhancement because exercise is both physically and mentally depleting. This article aims to (a) reinforce the efficacy of creatine supplementation in athletes, (b) showcase creatine's role as a cognitive enhancer, and (c) establish the need for future interventions in creatine's effect as a comprehensive ergogenic aid (combining physical and cognitive benefits).